Leadership styles and qualities of the head as the main components of effective management of the social service under martial law conditions - Puzyrova, Olha (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2022)
The article is devoted to the review and analysis of the types of management styles and qualities of the head ofthe social service. The importance of studying changes in the system of relations «The head – The subordinate» isjustified in view of certain problems and difficulties in the work of social services under martial law conditions inUkraine.The article uses methods of analysis and generalization to clarify the definition of the term “leadership styles”as well as groups important personal and professional qualities of the head. The empirical basis of the article is resultsof in-depth interviews conducted with the heads of social services, public organizations and charitable foundations,implemented within the scientific theme «Actual directions of management of social services» of the Department ofSociology of Management and Social Work of V. N. Karazin Kharkiv National University. According to the results ofthe research, several groups of qualities of the head (professional, leadership, personal and communicative) wereformed by author, which are relevant for the realization of managerial influence under conditions of stable situation andduring the period of martial law in the country.Based on the analysis of the advantages and disadvantages of different management styles, the authorconcluded that it is necessary to situationally apply a set of techniques and methods of management which inherent indemocratic and directive styles in war conditions. The results of empirical research have proved that in the conditions ofthreats and risks, limited recourses, high workload on employees, the role of the complex of leadership qualities of thehead is significantly increased.A head-leader must be able to not only to organize work activities and regulate formal labor relations, but alsoto inspire employees, encourage them to achieve goals and maintain positive social and psychological atmosphere in theorganization. Personal characteristics of the manager, such as empathy, humanity and attention to subordinates, havebecome important for the moral and psychological support of service personnel in wartime, when, in addition todifficulties arising in the labor process, there is a real threat to safety and life.